Associations of obesity-related indices with prediabetes regression to normoglycemia among Chinese middle-aged and older adults: a prospective study - Yang, Hongguang; Zhang, Minjie; Nie, Jiaqi; Zhang, Minzhe; Lu, Gaolei; Chen, Rui; He, Qiqiang (Frontiers in Nutrition, 2023)
Background: Prediabetes is associated with increased cardiovascular risk and all-cause mortality, while its regression will decrease the risks. This study investigated the associations of six obesity-related indices (waist-to-height ratio (WHtR), body roundness index (BRI), conicity index (CI), a body shape index (ABSI), Chinese visceral adiposity index (CVAI) and triglyceride glucose (TyG) index) with prediabetes regression based on the China Health and Retirement Longitudinal Study (CHARLS) enrolling middle-aged and older adults. Methods: We included 2,601 participants with prediabetes from CHARLS, who were followed up from 2011-2012 to 2015-2016, with blood samples collected for measuring fasting plasma glucose and haemoglobin A1c. All the obesity-related indices at baseline and their dynamic changes were calculated and categorized into tertiles. Logistic regression analysis was applied to obtain the odds ratio (OR) and 95% confidence intervals (CIs). Attribution fractions (AFs) and 95%CIs of these indices and the dynamic changes were calculated with the AF package in R software and the cutoff values of initial obesity-related indices were obtained by receiver operating characteristic (ROC) analysis. Results: During the 4-year follow-up period, 562 (21.61%) participants regressed from prediabetes to normoglycemia. They had lower initial BRI, WHtR, CI, ABSI, CVAI and TyG than those who did not (P < 0.05). After multivariable adjustment, participants in the first tertile of initial BRI (OR, 1.45, 95%CIs, 1.09~1.93), WHtR (OR, 1.46, 95%CIs,1.10~1.95) and CVAI (OR, 1.47, 95%CIs, 1.11~1.93) had increased odds of prediabetes regression compared with those in the highest tertile. Participants with decreased TyG (OR, 2.08; 95%CIs, 1.61~2.70) also had increased odds of prediabetes regression compared with those with increased TyG. The cutoff values of initial obesity-related indices were 4.374 for BRI, 0.568 for WHtR, 8.621 for TyG, 1.320 for CI, 0.083 for ABSI and 106.152 for CVAI, respectively. The AFs were 21.10% for BRI<4.374, 20.85% for WHtR<0.568, 17.48% for CVAI<107.794 and 17.55% for ∆TyG<0, respectively. Conclusion: Low initial BRI, WHtR and CVAI, as well as TyG reduction were significantly related to prediabetes regression to normoglycemia and the PAFs were around 20%. Less abdominal fat and IR reduction would benefit future health outcomes among people with prediabetes.